Mekanisme Pemungutan Bea Perolehan Hak Atas Tanah Dan Bangunan Atas Perolehan Warisan Di Badan Keuangan Daerah Kabupaten Boyolali - LMS Kristiyanti (Jurnal Akuntansi dan Pajak, 2021)
Fees for obtaining land and building is one kind of local taxes to be optimized. Fees for obtaining land and building rights are taxes on the acquisition of land and building rights stipulated in law No.28 of 2009 concerning regional taxes and levies. Inheritance is the acquisition of rights to land and buildings by the heirs of the heirs (owner of land and buildings) that apply after the heir dies. The aim is to find out how the collection mechanism for the acquisition of rights to land and buildings in the Boyolali district financial institution.